Consumers’ intention to visit green hotels – a goal-framing theory perspective - Wang, Lei; Wang, Zi-Xu; Zhang, Qi; Jebbouri, Abdelhamid; Wong, Philip, P. W. * (Routledge, 2021)
The theory of planned behaviour (TPB) and value-belief-norm (VBN) theory are recognised as powerful predictive models to explain consumers’ green purchase behaviour (GPB). The models were frequently used for predicting consumers’ green hotel visitations in previous studies. However, an unresolved research gap exists in green hotel literature concerning consumer attitude and behaviour in determining whether TPB or VBN possess inherent disadvantages in predicting GPB. The latest studies identified the goal-framing theory as an appropriate integrative framework to understand consumer GPB compared to the TPB and VBN. Nevertheless, only limited studies applied and tested the goal-framing theory in determining green hotel selection. This study revealed that the goal-framing theoretical framework has a higher predictive capacity than TPB and VBN in predicting consumer green hotel visit intention. The findings indicated a positive correlation between gain goal-frame, normative goal-frame, hedonic goal-frame, and intention. Furthermore, the results showed a positive relationship between subjective norm, attitude and personal norm. The results also demonstrated how consumers’ intentions are derived from gain goal-frame, normative goal-frame (except altruism), and hedonic goal-frame dimensions and how subjective norms influence attitude and personal norm. Lastly, the theoretical and practical implications and limitations were discussed.